2013
DOI: 10.1371/journal.pone.0059543
|View full text |Cite
|
Sign up to set email alerts
|

Boron Stress Responsive MicroRNAs and Their Targets in Barley

Abstract: Boron stress is an environmental factor affecting plant development and production. Recently, microRNAs (miRNAs) have been found to be involved in several plant processes such as growth regulation and stress responses. In this study, miRNAs associated with boron stress were identified and characterized in barley. miRNA profiles were also comparatively analyzed between root and leave samples. A total of 31 known and 3 new miRNAs were identified in barley; 25 of them were found to respond to boron treatment. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 60 publications
4
55
0
2
Order By: Relevance
“…However, several genes have been found to be regulated by B levels, suggesting that plants possess mechanisms to sense, respond to, and maintain B homeostasis, either directly or indirectly (Kobayashi et al, 2004;Takano et al, 2006;Camacho-Cristóbal et al, 2008;Ozhuner et al, 2013;Abreu et al, 2014). Most notable, however, is the fact that B is proposed to play an important role in organisms lacking cell walls such as zebra fish and mice, suggesting that there are other functions for B that remain unresolved (Lanoue et al, 1998;Bennett et al, 1999;Rowe and Eckhert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, several genes have been found to be regulated by B levels, suggesting that plants possess mechanisms to sense, respond to, and maintain B homeostasis, either directly or indirectly (Kobayashi et al, 2004;Takano et al, 2006;Camacho-Cristóbal et al, 2008;Ozhuner et al, 2013;Abreu et al, 2014). Most notable, however, is the fact that B is proposed to play an important role in organisms lacking cell walls such as zebra fish and mice, suggesting that there are other functions for B that remain unresolved (Lanoue et al, 1998;Bennett et al, 1999;Rowe and Eckhert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…MiR319 , previously known as ‘miR-JAW’, was firstly described in Arabidopsis because of its role in controlling leaf morphogenesis [20], [21]. It has been reported that miR319 targeted TEOSINTE BRANCHED/CYCLOIDEA/PCF (TCP) genes, the plant-specific transcription factors containing bHLH motifs that allow DNA binding and protein-protein interaction [22], [23], [24], [25], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR408 is responsive to various environmental factors, e.g. copper, light, boron, water deficit, and salinity (Yamasaki et al, 2007;Trindade et al, 2010;Ozhuner et al, 2013;Mutum et al, 2013;Feng et al, 2013;Jovanovi c et al, 2014;Zhang et al, 2014;Hajyzadeh et al, 2015). Previous studies have indicated that plantacyanin, laccases, AFG1, and TaCLP1 are genuine targets of miR408 (Wang et al, 2004;Zhang et al, 2006;Abdel-Ghany and Pilon, 2008;Feng et al, 2013;Ozhuner et al, 2013).…”
mentioning
confidence: 99%